Biodynamics of HCV infection in haemodialysis patients in Pahang - Mustafa Mahmoud, Mohammed Imad Al-Deen; Abdul Majid, Mohammed Saad; Hamzah, Hairul Aini; Hasmoni, Mohamed Hadzri (Elsevier, 2010)
Background: Hepatitis C is a global disease, WHO has described it as a “viral time bomb”. In Malaysia, the sero-prevalence is 1.6%. HCV infection is frequent in patients undergoing maintenance haemodialysis, with prevalence between 8 and 10%. Hepatitis C has an adverse effect on both patient and graft survival in those who get renal transplants. There are relatively scarce reports on the natural fluctuation in viral load and alpha interferon (&-IFN) level in patients on chronic hemodialysis